DRN2025 Drawing Negation Political Space - Deborah Harty (2025)
Recording of the final in a series of 2025 Drawing Research Network (DRN) symposia exploring the theme Drawing Negation. This event was organised by members of the Drawing Research Group (DRG) at Loughborough University, chaired by Deborah Harty. The session included presentations of practice research investigating 'Political Space' from Constança Arouca, Claire Anscomb (DeMontfort University) and Cao Zhehao (UCA) and was chaired by DRG member and Doctoral Researcher Rachel Gadsden-Hayton.